SINERGI AKADEMISI DAN KOMUNITAS: MEMBANGUN KESADARAN INKLUSIF TERHADAP ODGJ DAN DISABILITAS FISIK DI LINGKUNGAN SOSIAL MELALUI PENGUATAN LITERASI - Sri Wahyuningsih; Cahyo Indarto; Jamiatus Syarifah Amaliya; Indah Dwi Prasetya Ningsih (Dharma: Jurnal Pengabdian Masyarakat, 2026)
Stigma and discrimination against people with mental disorders (PWDs) and individuals with physical disabilities remain major obstacles in creating an inclusive society in Indonesia. The low level of public literacy on mental health and disabilities often leads to rejection, social exclusion, and unequal treatment. This community service activity aims to build inclusive awareness through the synergy between academics and local communities using an educational and participatory approach. The methods employed include social literacy education through training, group discussions, empathy campaigns, and community-based assistance. Academics act as facilitators in preparing literacy materials and empathetic communication training, while the community serves as active partners in implementing activities within the social environment. The results of the activities indicate an increased public understanding of the concept of social inclusion, as well as the rights of people with mental disorders and individuals with physical disabilities.